Vitamin C Transporters in Cancer: Current Understanding and Gaps in Knowledge - Wohlrab, Christina; Phillips, Elisabeth; Dachs, Gabi U. (Frontiers in Oncology, 2017)
Sufficient uptake and whole body distribution of vitamin C (ascorbate) is essential for many biochemical processes, including some that are vital for tumor growth and spread. Uptake of ascorbate into cancer cells is modulated by availability, tumor blood flow, tissue diffusion parameters and ascorbate transport proteins. Uptake into cells is mediated by two families of transport proteins, namely the SLC23 family, consisting of sodium-dependent vitamin C transporters (SVCTs) 1 and 2, and the SLC2 family of glucose transporters (GLUTs). GLUTs transport the oxidized form of the vitamin, dehydroascorbate (DHA), which is present at negligible to low physiological levels. SVCT1 and 2 are capable of accumulating ascorbate against a concentration gradient from µM concentrations outside to mM levels inside of cells. Investigating the expression and regulation of SVCTs in cancer has only recently started to be included in studies focused on the role of ascorbate in tumor formation, progression and response to therapy. This review gives an overview of the current, limited knowledge of ascorbate transport across membranes, as well as tissue distribution, gene expression and the relevance of SVCTs in cancer. As tumor ascorbate accumulation may play a role in the anti-cancer activity of high dose ascorbate treatment, further research into ascorbate transport in cancer tissue is vital.